Breaking New Ground With Endoxifen: Augmentation Strategies in OCD Management—A Case Series - Rishabh Singh; Markanday Sharma; Samiksha Sahu; Arka Adhvaryu (Case Reports in Psychiatry)
Obsessive–compulsive (OC) disorder (OCD) is a common and potentially disabling illness with a waxing and waning course. OCD significantly disrupts the quality of life. Selective serotonin reuptake inhibitors (SSRIs) are first-line pharmacological treatments for OCD and benefit up to half of the patients. Augmentation with low-dose antipsychotics is an evidence-based second-line strategy. Psychotherapy, including cognitive behavior therapy (CBT), is used both as first and second-line treatment. A significant portion of patients, however, do not respond to conventional treatments. We present a case series on the use of Endoxifen as an augmenting agent in patients with OCD and multiple psychiatric comorbidities who did not respond well to conventional pharmacotherapy.